1999
DOI: 10.1051/forest:19990201
|View full text |Cite
|
Sign up to set email alerts
|

Above- and belowground phytomass and carbon storage in a Belgian Scots pine stand

Abstract: We investigated the storage of carbon (C) in the soil, litter and various phytomass compartments in a 69-year-old Scots pine (Pinus sylvestris L.) stand in the Belgian Campine region, Brasschaat, Belgium. The total amount of C stored in the stand was 248.9 t•ha-1 , 47 % of which was in soil organic matter, 11 % in surface litter and 42 % in phytomass. More than 60 % of total C was stored belowground. Total phytomass C in the stand was 104 t•ha-1 ; most phytomass C was found in the stems (70 %). The root system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
107
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 20 publications
12
107
0
Order By: Relevance
“…in the oak-beech stand and ash in the ash stand, accounted respectively for 84.0% and 66.4% of the total aboveground carbon stock. Carbon storage in the aboveground biomass of the Aelmoeseneie forest is comparable with the values found in previous studies [6,15,27,34,41]. Dutch investigators [25] showed that the carbon stock in living biomass is largest for beech forests, a conclusion comparable to results found here.…”
Section: Aboveground Carbon Poolssupporting
confidence: 92%
See 2 more Smart Citations
“…in the oak-beech stand and ash in the ash stand, accounted respectively for 84.0% and 66.4% of the total aboveground carbon stock. Carbon storage in the aboveground biomass of the Aelmoeseneie forest is comparable with the values found in previous studies [6,15,27,34,41]. Dutch investigators [25] showed that the carbon stock in living biomass is largest for beech forests, a conclusion comparable to results found here.…”
Section: Aboveground Carbon Poolssupporting
confidence: 92%
“…Dutch investigators found similar, but slightly lower values ranging from 102 to 122 tons C ha -1 for comparable forest ecosystems [26] while Janssens et al [15] found a carbon content of 114.7 tons ha -1 over a depth of 1 m in a Belgian Scots pine forest. The forest they examined was, however, situated on a sandy soil.…”
Section: Mineral Soilmentioning
confidence: 92%
See 1 more Smart Citation
“…These BEFs s.l. fulfilled the conditions stated above, and were reported by (at least one of) the following authors: Baritz and Strich [4], Bartelink [5,6], COST-E21 [13], Dieter and Elsasser [15], Grote [19], Guilley et al [20], Houghton et al [21], IPCC [25], Janssens et al [27] [53]. BEFs s.l.…”
Section: Biomass Expansion Factors Slmentioning
confidence: 73%
“…heathland small areas were cultivated and ploughed, and some others were not, but there should have never been forest in the past 1000 years in place where the stands are growing. Basic information on the sites are given in Table 1, while a more detailed description of the stands can be found in Janssens et al (1999) andCuriel Yuste et al (2005a).…”
Section: Site Descriptionmentioning
confidence: 99%